How to solve 4x - 3 = 0? Get the answer and stepwise instruction to solve linear equation in one variable 𝒙.

#### Steps for finding the solution

We have 4**x** - 3 = 0

First, we move the *non ***x** terms to the RHS of the equation. To do this, we add 3 to both sides.

**Note: ** if a = b, then a + c = b + c

Therefore, 4**x** - 3 + 3 = 0 + 3

or, 4**x** = 3

Next, divide both sides by 4, which is the coefficent of **x**

**Note: ** if a = b, then a ÷ c = b ÷ c

4**x**/4 = 3/4

**x** = 3/4 or, **x** = 0.75